Peranan Pantun Dalam Pendidikan Islam Pada Masyarakat Desa Klambir V - Alfin Fernando; Nur Sakinah; Aris Firjatullah Pratama; Osama Mukhlisin (Yayasan Rahmat Islamiyah, 2023)
The purpose of writing this scientific paper is to determine how big the role of pantun is in the aspect of Islamic education, especially in the village of Klambir V, as we know Islam coming to Indonesia did not change customs but how these customs can adapt to Islamic cultural values. The relationship between Islam and literature contains beautiful poems, advice and meanings that cannot be separated from the value of culture itself. The research method used by the author is a qualitative method, in which the author goes directly to observation, interviews and inputting data to the Klambir V village community.